2018
DOI: 10.1002/hep.29477
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo‐controlled trial of cenicriviroc for treatment of nonalcoholic steatohepatitis with fibrosis

Abstract: The aim of this study was to evaluate cenicriviroc (CVC), a dual antagonist of C—C chemokine receptor types 2 and 5, for treatment of nonalcoholic steatohepatitis (NASH) with liver fibrosis (LF). A randomized, double‐blind, multinational phase 2b study enrolled subjects with NASH, a nonalcoholic fatty liver disease activity score (NAS) ≥4, and LF (stages 1‐3, NASH Clinical Research Network) at 81 clinical sites. Subjects (N = 289) were randomly assigned CVC 150 mg or placebo. Primary outcome was ≥2‐point impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
479
2
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 570 publications
(499 citation statements)
references
References 21 publications
13
479
2
5
Order By: Relevance
“…However, adverse effects may limit the treatment potential, e.g., glitazones are associated with phenotypical weight gain [136] and obeticholic acid induced pruritus and elevated LDL-C [137], the latter a potential concern in patients already at risk for cardiovascular disease. Cenicriviroc—despite not meeting its primary endpoint of NAFLD activity score improvement—[138] and obeticholic acid [137] were both able to improve hepatic fibrosis, and were currently undergoing phase III investigation. In addition, promising results have been reported for several phase II clinical trials and additional trials are currently ongoing, reflecting the growing research effort in developing novel treatments for NASH.…”
Section: Pre-clinical Models and Current Clinical Managementmentioning
confidence: 99%
“…However, adverse effects may limit the treatment potential, e.g., glitazones are associated with phenotypical weight gain [136] and obeticholic acid induced pruritus and elevated LDL-C [137], the latter a potential concern in patients already at risk for cardiovascular disease. Cenicriviroc—despite not meeting its primary endpoint of NAFLD activity score improvement—[138] and obeticholic acid [137] were both able to improve hepatic fibrosis, and were currently undergoing phase III investigation. In addition, promising results have been reported for several phase II clinical trials and additional trials are currently ongoing, reflecting the growing research effort in developing novel treatments for NASH.…”
Section: Pre-clinical Models and Current Clinical Managementmentioning
confidence: 99%
“…Although current anti‐inflammatory approaches have yet to bear fruit in BA, it is possible that there are subsets of BA patients who would benefit from selective agents after detailed cellular and molecular immunotyping. Several antifibrotic agents are currently undergoing study in liver diseases, including the chemokine (C‐C motif) receptor 2/5 antagonist cenicriviroc, which has improved fibrosis in nonalcoholic steatohepatitis in the recently completed CENTAUR trial …”
Section: Innovative Approaches To Treatmentmentioning
confidence: 99%
“…For example, cenicriviroc, a dual CCR2/CCR5 antagonist improved hepatic inflammation and fibrosis in a murine model of NASH. 77 A phase IIb trial of cenicriviroc in patients with NASH patients with fibrosis 78 showed improvement of fibrosis without worsening of steatohepatitis. Furthermore, the pharmacological MLK3 inhibitor URMC099 reduced circulating CXCL10 and attenuated murine NASH.…”
Section: Clinical Implications and Therapeutic Strategiesmentioning
confidence: 99%